Möglichkeiten und Grenzen der Messung interkultureller Kompetenz - Błażek, Agnieszka (Glottodidactica, 2007)
There is no doubt that a cultural dimension is a part of the foreign language teaching. Still, the necessity of assessing learners' intercultural competence seems to be overlooked. The following article examines possibilities of assessing intercultural competence implying not only quantification and judgment but also reflecting the effectiveness of intercultural foreign language teaching. The paper gives also an insight into the limits of such kind of assessment.